Special Features of Acute Respiratory Infections Clinical Course in Children with Allergic Disorders: Problems of Management and Ways to Solve Them - N. B. Migacheva; T. I. Kaganova; A. V. Aronova (Вопросы современной педиатрии)
Acute respiratory infections are one of the most topical problems in pediatrics due to their high prevalence, especially among certain children groups. Allergic disorders represent one of the most common causes of increased susceptibility of children to viral infections, more severe clinical course, high risk of complications and allergic responses to the drugs. Special characteristics of immune response of children with atopia influencing on the type of acute respiratory diseases clinical course are discussed in this article, as well as the main problems of management of such children are listed and the possible ways to solve these problems are offered.